Mie Hijau Daun Katuk Sebagai Upaya Pencegahan Stunting Dusun Jati Lor, Desa Tonoboyo, Kecamatan Bandongan - Widiyanto, Andi; Anas Raihan Arifuddin; Nadhifa Nur Oktavia; Novi Fitriyani; Jovanka Hayyu Kurnia Putri; Hafid Abdul Haris (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Stunting is a condition of height and growth in children that is not in accordance with age, this calculation uses the Z-index score of height for age. The factor that causes stunting is the lack of nutritional intake that starts from the womb to the beginning of the child's life (First 1,000 Days of Birth) This factor is caused by a lack of access to healthy and nutritious food and a lack of vitamin and mineral intake needed by pregnant women. This community service activity uses the Participatory Rural Appraisal (PRA) approach method by involving the active role of the community in the implementation of community service activities. The implementation of activities carried out includes socialization of stunting prevention, processing katuk leaves into green noodles for pregnant and lactating women, and finally planting katuk tree seedlings around residents' homes. The results of measuring community knowledge increased to 80.7% from the previous 43.4% through questionnaires before and after the activity was carried out.